Varicose Veins - de Oliveira Esteves, Alexandre; Burgos Garcia, Carolyn; Furtado Neves, Pedro Juan; Abreu, Phillipe; de Oliveira Leite, Tulio Fabiano; Bertanha, Matheus [UNESP]; Malgor, Rafael (Springer Nature, 2025)
Lower limb varicose veins are present in a significant portion of the population with an estimated prevalence of 47.6% of the general population, with a predominance of females, being a constant complaint in clinical practice [3].